PERANCANGAN SISTEM INFORMASI AKUNTANSI PENJUALAN TUNAI PADA TOKO RIR OUTDOOR CIBUNGUR PURWAKARTA - Nurrahman, Dede; Suhardi, Suhardi; Permana, Egitya; Sugiyanto, Sugiyanto; Suhardi (Sistem Informasi Akuntansi Kampu Kabupaten Karawang, 2021)
Abstracts - In the world of commerce the ability to process data and use Information in efficiency and effectiveness is very important for companies, especially in the company's sales information system itself. At the RIR Outdoor Store, they also really need an information system that shows and provides satisfactory service to consumers. For this reason, the author tries to make a Final Project regarding the cash sales system at the RIR Outdoor Store, which is still conventional. At this time the system in the RIR Outdoor Store itself is still done manually, starting from sales, ordering goods, recording customer data and making reports. So it is possible when the process occurs an error in recording, storing data and reports that are made inaccurate. With a computerized system is the best solution to solve the problems that exist in the RIR Outdoor Store, and with a computerized system that can achieve an activity that is effective and efficient in enforcing activities in this company. Therefore, the computerized system is better than the manual system to run more effectively and efficiently, and the current goods sales system is more conducive than the previous system.